Associations of Treatment Effort, Economic Income, and Accessibility with the Utilization of Herbal Medicine in Medan City - Sri Lestari Ramadhani Nasution; Muhammad Rezebri; Ermi Girsang (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Herbal medicine has gained increasing attention as a complementary or alternative medicine in many countries, including Indonesia, where it is deeply rooted in cultural practices and supported by government policies. This study aimed to determine the association between treatment effort, economic income, and accessibility with herbal medicine utilization in Medan City. The research location was Medan City and the research time was from January to March 2025. Using a cross-sectional design, 369 respondents were selected through stratified proportional sampling. Independent variables are type of treatment business, economic income, and accessibility, while the Dependent Variable is the utilization of herbal treatment which has been tested for validity with five question items each on each variable. Data were collected through a structured questionnaire and analyzed using the chi-square test using IBM SPSS Version 29.0. The results showed that accessibility was the only variable significantly (p = 0.011; PR = 1.77, 95% CI: 1.14-2.76) associated with herbal medicine use. Respondents who reported frequent access to herbal products and services were more likely to use them regularly. In contrast, treatment effort and economic income were not significantly associated with utilization. These findings suggest that improving accessibility-through regulation, education, and service availability-is key to increasing the reach and legitimacy of jamu. Policy recommendations include integrating jamu services into the formal health system, ensuring quality control of jamu products, and promoting community-based education to build trust and informed use. Strengthening these structural supports can help bridge healthcare gaps and maintain the cultural relevance of traditional medicine in urban settings. Keywords: Herbal Medicine Accessibility, Economic Income, Treatment Effort, Public Health Behavior.